2017
DOI: 10.1093/annonc/mdx275
|View full text |Cite
|
Sign up to set email alerts
|

A phase III trial comparing oral S-1/cisplatin and intravenous 5-fluorouracil/cisplatin in patients with untreated diffuse gastric cancer

Abstract: NCT01285557.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 12 publications
0
38
1
Order By: Relevance
“…The FLAGCS [8,10], a multicenter randomized phase 3 clinical trial, also showed no difference between the 2 chemotherapies in terms of PFS (95% CI: 0.86-1.14, p = 0.92) and OS (95% CI: 0.80-1.05, p = 0.20). The other 2 RCTs (Li et al [11], Ajani et al [12]) also reported the same outcomes. Accordingly, we concluded that PS was comparable to PF in terms of OS and PFS.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The FLAGCS [8,10], a multicenter randomized phase 3 clinical trial, also showed no difference between the 2 chemotherapies in terms of PFS (95% CI: 0.86-1.14, p = 0.92) and OS (95% CI: 0.80-1.05, p = 0.20). The other 2 RCTs (Li et al [11], Ajani et al [12]) also reported the same outcomes. Accordingly, we concluded that PS was comparable to PF in terms of OS and PFS.…”
Section: Discussionmentioning
confidence: 70%
“…After selection, 6 RCTs containing 1,736 participants (PS group: 935 participants; PF group: 801 participants) were ultimately included in our analysis ( Fig. 1) [8,[10][11][12][13][14]. Although both Ajani et al [8] and Ajani et al [10] were analyzed for the FLAGCS trial, Ajani et al [8] uniquely included outcomes of PFS, ORR, and TTF, and several AEs were provided by Ajani et al [10]; thus, both articles were included in our analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations